Sell, sell, sell or learn, learn, learn? The EdTech market in New Zealand's education system – privatisation by stealth?. Issue 1 (1st January 2017) - Wright, Noeline; Peters, Michael
ABSTRACT: An article in The Atlantic 'Quantifying the Ed-Tech Market' (2015), which draws on a review by the Education Technology Industry Network, reports that the U.S. Ed-tech market totalled 8.38 billion in the 2012–2013 academic year, which is up from 7.9 billion the year before, and up 11.7 per cent from 2009. K-12 online course revenue including any digital curriculum increased some 320% and the testing and assessment market, the largest single category, generated 2.5 billion. The New Zealand business organisation EDTechNZ, indicates on its website that educational technology is the fastest growing sector of a global smart education market worth US100 billion, forecast to grow to US394 by 2019. The same source indicates that Cloud-based educational technology is accelerating at 20% growth per annum and is forecast to reach US12 billion by 2019. These returns are unequalled by most other economic sectors. Our concern in this article is that the market imperative based on selling has become a driving logic for digital technologies in schools while learning gets lost in the rush for companies to profit from schools, creating de facto privatisation by stealth. Aspects of the New Zealand educational context are used to illustrate our thinking, especially since most educational provision is still state owned and taxpayer funded.